2014
DOI: 10.1063/1.4891251
|View full text |Cite
|
Sign up to set email alerts
|

A self-consistent thermodynamic model of metallic systems. Application for the description of gold

Abstract: A self-consistent thermodynamic model of metallic system is presented. The expression for the Gibbs energy is derived, which incorporates elastic (static) energy,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 55 publications
(95 reference statements)
0
12
0
Order By: Relevance
“…Anderson et al, 1989;Shim et al, 2002;Tsuchiya, 2003;Yokoo et al, 2009); a remarkably good agreement between calculated and experimental values is observed even at the highest temperatures. However, Balcerzak et al (2014) report calculated specific heat values that are different by up to 3% from the experimental results, where for T near T m , the calculated specific heat is slightly higher than the experimental one. The same tendency has been observed by Yokoo et al (2009).…”
Section: Thermal Expansion and Heat Capacity Of Goldmentioning
confidence: 64%
See 1 more Smart Citation
“…Anderson et al, 1989;Shim et al, 2002;Tsuchiya, 2003;Yokoo et al, 2009); a remarkably good agreement between calculated and experimental values is observed even at the highest temperatures. However, Balcerzak et al (2014) report calculated specific heat values that are different by up to 3% from the experimental results, where for T near T m , the calculated specific heat is slightly higher than the experimental one. The same tendency has been observed by Yokoo et al (2009).…”
Section: Thermal Expansion and Heat Capacity Of Goldmentioning
confidence: 64%
“…In our analysis we did not include the electronic contribution to the specific heat as it is small and did not improve the fit at high temperatures. Balcerzak et al (2014) reported that the electronic contribution amounts to 0.3% and up to 3.5% of the total specific heat at 100 and 1300 K, respectively, but according to Cordoba & Brooks (1971) the electronic contribution is only 0.1% at 1330 K.…”
Section: Thermal Expansion and Heat Capacity Of Goldmentioning
confidence: 99%
“…(14) and (15) can be calculated for T > T D /(2π) by the approximate method (as in Ref. [40]) using Bernoulli series. On the other hand, for the whole temperature range the integral can be calculated either by the direct numerical integration, or by the exact method as, for instance, presented in Ref.…”
Section: Lattice Subsystemmentioning
confidence: 99%
“…The vibrational energy is taken in the Debye approximation and its form can appear in two variants: for low temperatures only, and in the whole temperature range. In the low temperature limit the free energy is given by the formula [40]:…”
Section: Lattice Subsystemmentioning
confidence: 99%
“…In the paper the total grand potential has been constructed for the dimer system, in which the magnetic, elastic and thermal vibration energies play important roles. The similar attempts at the total Gibbs energy construction, i.e., consisting in summation of various energy contributions, have been undertaken, so far, for the bulk materials [61,[63][64][65][66]. According to our knowledge, for the Hubbard dimer such method has not been presented previously.…”
Section: Discussionmentioning
confidence: 99%